Mono-fluorinated alkyne-derived SAMs on oxide-free Si(111) surfaces preparation, characterization and tuning of the Si workfunction - Pujari, Sidharam P (Langmuir : the ACS journal of surfaces and colloids, 2013)
Organic monolayers derived from ω-fluoro-1-alkynes of varying carbon chain lengths (C(10)-C(18)) were prepared on Si(111) surfaces, resulting in changes of the physical and electronic properties of the surface. Analysis of the monolayers using XPS, Infrared Reflection Absorption Spectroscopy, ellipsometry and static water contact angle measurements provided information regarding the monolayer thickness, the tilt angle, and the surface coverage. Additionally, PCFF molecular mechanics studies were used to obtain information on the optimal packing density and the layer thickness, which were compared to the experimentally found data. From the results, it can be concluded that the monolayers derived from longer chain lengths are more ordered, possess a lower tilt angle, and have a higher surface coverage than monolayers derived from shorter chains. We also demonstrate that by substitution of an H by F atom in the terminal group, it is possible to controllably modify the surface potential and energy barrier for charge transport in a full metal/monolayer-semiconductor (MOMS) junction